The Nature of Biology in Life Sciences Undergraduate Courses - Ana Júlia Soares Santana; Maria Danielle Araújo Mota; Ana Paula Solino; Raquel Crosara Maia Leite (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
The research deals with the relationship between the initial training of biology teachers and the Nature of Biology, aiming to analyze the Pedagogical Projects of two Undergraduate Courses in Biological Sciences of a university in northeastern Brazil in search of the Nature of Biology. The methodology adopted was qualitative with exploratory purpose based on documentary research, in which the menus of the disciplines of the chosen courses were analyzed, the data collected were processed through discursive textual analysis. The results obtained pointed to the presence of the Nature of Biology in the courses of degree in Biological Sciences in the specific disciplines of Biology and pedagogical.